RADIATION HYGIENE: INTERACTION OF SCIENCE AND PRACTICE - S. I. Ivanov; N. A. Akopova; A. V. Baranov; E. P. Ermolina (Радиационная гигиена, 2017)
A short sketch of history of radiation hygiene formation as a scientific discipline is presented, its conventional directions are outlined, and the perspectives of development are pointed out. Examples of co-operation of scientists and specialists in health protection practice in the field of radiation hygiene are presented.